The Position of the Attorney General’s Office as the Single Prosecutor in Indonesia’s Criminal Justice System - Irwan, Muhammad; Suprapto, Suprapto; Zulaeha, Mulyani; Faishal, Achmad (Scholar Center, 2025)
This study aims to critically examine the institutional position of the Public Prosecutor’s Office as the sole prosecutorial authority (single prosecutor) within the Indonesian criminal justice system. The core legal issue addressed concerns the authority and functional role of the Prosecutor’s Office as the exclusive body responsible for prosecution, particularly as mandated in Article 1 of Law No. 11 of 2021, which amends Law No. 16 of 2004 on the Public Prosecutor's Office of the Republic of Indonesia. Employing a normative legal research method, this study focuses on the analysis of normative ambiguity, using both statutory and conceptual approaches. The findings indicate that the single prosecutor concept normatively reinforces the centralization of prosecutorial powers in the hands of the Public Prosecutor's Office. Nonetheless, ambiguities persist regarding the interpretation of the limits of this authority, especially in its interactions with other law enforcement agencies and in the practical implementation of the dominus litis principle. Therefore, a comprehensive legal interpretation is imperative to prevent overlapping jurisdictions and to uphold the coherence and consistency of Indonesia’s criminal justice system.